Assessing the perspective of well-being of older patients with multiple morbidities by using the LAVA tool: a person-centered approach - Wild, Beate; Wurmbach, Viktoria; Böhlen, Friederike; Kusch, Marcel; Seidling, Hanna; Reich, Paul; Hartmann, Mechthild; Haefeli, Walter E.; Friederich, Hans-Christoph; Slaets, J. (BMC geriatrics, 2021)
Older patients with multiple morbidities are a particularly vulnerable population that is likely to face complex medical decisions at some time in their lives. A patient-centered medical care fosters the inclusion of the patients’ perspectives, priorities, and complaints into clinical decision making.
Gesehen am 15.09.2021